The effects of footwear on force production during barbell back squats Part II: Standardizing squat depth - Zobeck, C. J.; Senchina, D. S. (International Journal of Research in Exercise Physiology, 2020)
Introduction: Data concerning the advantages or disadvantages of using weightlifting shoes (compared to normal athletic or running shoes) for performing back squats has been largely equivocal. A recent review has suggested that a lack of standardization across studies has made it difficult to draw generalizations and may obscure any footwear effects. Therefore, the purpose of this study was to replicate the methods of a previously published study, except this time strictly controlling for squat depth. Methods: Eleven male college athletes (20 ± 1 yrs) performed back squats in three conditions: 1) weightlifting shoes, 2) running shoes, or 3) running shoes with an external heel elevation (which made them equivalent in heel elevation to the weightlifting shoes). Knee angles, forefoot force production, and rearfoot force production were measured during squats. Lifters` perceptions of shoe comfort and stability were measured after each condition. Static ankle goniometry was measured at rest for each condition as an internal "negative control". Results: No significant differences were found for any of the variables across any of the footwear conditions. Conclusions: These results are substantively similar to the aforementioned study that did not standardize squat depth, suggesting squat depth standardization may not have impacted the measured outcomes. Lifters` previous experience and set motor patterns may explain the results.